A look inside Renewed World Energies' algae bioreactor - Armstrong, Richard (Chemical engineer) (Knovel, 2010)
Sustainable Energy & Development. Renewed World Energies applies time-tested engineering strategies to the design of its cutting-edge algae bioreactor.
Title from title page (viewed September 3, 2010).
Keywords: Algae -- Biotechnology.; elektronické knihy; electronic books